No Emergent Resistance in HIV-1 Infected Virologically-Suppressed Subjects Who Switched to R/F/TAF. (4th October 2017) - Porter, Danielle; Kulkarni, Rima; Cao, Huyen; Sengupta, Devi; White, Kirsten
Abstract: Background: GS-US-366-1216 and GS-US-366-1160 are randomized, double-blind, phase 3b studies evaluating the safety and efficacy of switching to rilpivirine/emtricitabine/tenofovir alafenamide (R/F/TAF) from R/F/tenofovir disoproxil fumarate (TDF) or efavirenz (EFV)/F/TDF, respectively, in HIV-1-infected virologically-suppressed subjects. At Week 48, switching to R/F/TAF was non-inferior to staying on R/F/TDF (94% vs. 94%, respectively) or EFV/F/TDF (90% vs. 92%) for HIV-1 RNA <50 c/mL (virologic success) by FDA snapshot analysis. Here, we present integrated resistance analyses of these two studies through Week 48. Methods: Historical genotypes were collected when available. Subjects in the resistance analysis population (subjects with HIV-1 RNA ≥400 c/mL at virologic failure, discontinuation, or Week 48) had genotypic/phenotypic analyses at failure for protease and reverse transcriptase (RT; PhenoSense GT, Monogram). Subjects with post-baseline resistance mutations detected had their baseline proviral DNA analyzed retrospectively (GenoSure Archive, Monogram). Results: Of the 1504 randomized and treated subjects, resistance development was analyzed for 7 subjects (0.9%; 7/754) on R/F/TAF, 1 subject (0.3%; 1/313) on R/F/TDF, and 2 subjects (0.5%; 2/437) on EFV/F/TDF. No R/F/TAF (0%) or R/F/TDF (0%) subjects developed primary NNRTI or NRTI resistance mutations. One EFV/F/TDF subject (0.2%; 1/437) developed primary NNRTI and NRTI resistance mutations (NNRTI: Y188L; NRTI: M184V). Three subjects on R/F/TAF had virologic rebound with mutations also detected at baseline by proviral DNA analysis. Historical genotypes were available for 527 subjects; virologic success rates were high among subjects with pre-existing mutations (Table 1). Conclusion: No emergent resistance to any of the components of R/F/TAF was detected through 48 weeks after switching. Virologic success rates were high among subjects with pre-existing mutations. Disclosures: D. Porter, Gilead Sciences, Inc.: Employee and Shareholder, Salary; R. Kulkarni, Gilead Sciences, Inc.: Employee and Shareholder, Salary; H. Cao, Gilead Sciences, Inc.: Employee and Shareholder, Salary; D. Sengupta, Gilead Sciences Inc.: Employee and Shareholder, Salary; K. White, Gilead Sciences, Inc.: Employee and Shareholder, Salary